Finite Element Modeling of Tin Slag Polymer Concrete Column with FRP Material Confinement under Compression - Muhamad Soffi, Manda; Mohd Ruzaimi, Mat Rejab; Shukur, Abu Hassan; Siti Safarah, Amirnuddin (Penerbit UTM, 2023)
One of the most current trends in Polymer Concrete (PC) material research is the Tin Slag Polymer Concrete (TSPC) study. After Faidzal et al. (2018) discovered that using Tin Slag (TS) waste as aggregates in PC, the strength achieved is comparable to ordinary concrete material, the investigation got underway. According to Bedi et al. (2014), PC is a superior alternative to cement-based concrete because of its great strength, durability, and strain resistance.